Contextual effects on the LSS implementation in networked service environments: A critical realism case study for the Port of Houston. Issue 5 (23rd September 2019) - Wang, Ping; Marley, Kathryn; Vogt, John Joseph; Mileski, Joan
Abstract : Purpose: The purpose of this paper is to investigate the contingency effects that contextual factors of a networked service environment have on the phased Lean Six Sigma (LSS) implementation frameworks. Design/methodology/approach: This paper employs the critical realism (CR) case study research methodology to examine the contingent and causal relationships between contextual configurations of business networks, the DMAIC or PDCA phases in an LSS implementation agenda, and business management functions. The authors conducted a single case study on the basis of challenges they met in kicking off lean transportation in the Port of Houston. Findings: The key finding from the study is a mid-range theory regarding the contingency effects of contextual factors of service business networks on the phased LSS implementation frameworks. The authors found that when there are complexity and dynamics of contextual factors at the field layer, management should focus more on tasks in early LSS phases to emphasize influencing. When there is no centralized authority in the network and the value-system is loosely coupled, management needs to execute more tasks as described in the define, measure and analyze phases with the purpose of both influencing and orchestrating. When individual actors have goals not aligned well with the goal of the business network and have unmatched operations capabilities, these factors should be considered as early as possible in these LSS phases. When a business network has complicated business processes with high unpredictability and uncertainty and individual actors' value-creation systems are not well embedded in the entire value-creation system, PDCA will be the preferred core structure of an LSS implementation agenda. Research limitations/implications: This study contributes to the LSS research stream by introducing a causal/contingency model that prescribes the contingency effects of three contextual configurations on LSS implementation. It also contributes to the emerging discipline, business network management, regarding how to use LSS frameworks in strategic planning. It also contributes to the CR school of problem-driven case study by using a strategic initiative framework as a platform and each phase in the framework as a unit. This conceptualization of the entity of interest helps explore the interactions among three theoretical constructs: contextual configurations, phased LSS implementation agenda and management functions. Practical implications: Managerial implications of this study are twofold. One is the procedure of analyzing the impacts of contextual factors on the causal relationships between LSS implementation phases and network management functions. The entire procedure represents the agenda-setting process of LSS implementation, the most daunting and challenging managerial task in LSS projects. Another one is the guideline on how to determine whether DMAIC or PDCA is appropriate for the LSS agenda when used in a networked environment. Originality/value: This paper would serve as an excellent resource for both academicians and LSS practitioners in initiating, orchestrating and managing an LSS project in a networked service environment. This study represents the first effort to explore the impact of contextual factors of business networks on lean transformation.